Exponential information’s extraction from power traces of modulo exponentiation implemented on FPGA - WU Zhen; CHEN Yun; CHEN Jun; WANG Min (Tongxin xuebao)
A power analysis model on modulo exponentiation’s computation suitable for real environment was presented in the basis of analysis to the great amount of power traces in the rough.And a method of signal processing for extracting exponential information from the initial power traces was inferred too.Hereby,a power analysis platform was designed and implemented.The exponential information submerged in power traces of 32bit modulo exponentiation algorithms applied in a FPGA chip was successfully extracted where after.Meanwhile,a conclusion about SPA attack on RSA made by Messerges et al,such as the problem with an SPA attack was that the information about the secret key was difficult to directly observe,was proved to be incorrect.Finally,the static masking algorithm for modulo exponentiation of anti-SPA attack was also validated in this testing platform.